Anti-Bacterial Properties of Boron Cross-linked Chitosan/Poly (Vinyl Alcohol) Hydrogels Containing Zinc Oxide Nanoparticles - Nanfang, Ida Doris Kobou (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2015)
Chitosan is a hydrophilic and versatile polysaccharide possessing functional groups such as carbonyl and amine groups which are areas for antimicrobial activity. PVA has high degree of swelling in aqueous solutions and mostly blended with chitosan because of its good tensile strength and elastic nature. Six chitosan- PVA hydrogel samples were prepared by varying the amounts of chitosan and PVA, blending them with equal amounts of boric acid ( cross-linker), soaking them in sodium hydroxide overnight, washed several times with distilled water, freeze- thawed at -200 for 6hrs and + 370 for 2hrs respectively for 5 cycles, then dried in an oven and later analyzed. During the hydrogel preparations, the first three samples were blended without zinc oxide nanoparticles and the last three with equal amounts of zinc oxide nanoparticles. Swelling percentages of samples 1- 3 were evaluated in 2 ways: (1) soaking a known amount of each dried sample in distilled water while varying time. (2) soaking another known amount of dried samples in different pH buffer solutions for 24hrs. Its kinetics showed that: as the pH increases, their swelling % increases and starts dropping as the pH gets more basic and that the higher the amount of PVA in a sample, the higher its swelling % in water with increased time. The bacterial analysis of the samples were carried out in order to determine the effect of an increased amount of chitosan and of zinc oxide nanoparticles on bacterial growth. The LB agar medium was used for the culturing of the E.coli bacteria which is a gram negative bacteria possessing a thinner peptidoglycan membrane. The sample with the highest amount of Chitosan showed more inhibition than the others and the addition of nanoparticles to this sample showed an even more greater inhibition towards the bacteria. Finally the Scanning electron microscopy (SEM) and FTIR of the prepared hydrogels were done inorder to determine the surface structures of the hydrogels and the various functional groups present in each hydrogel respectively. Keywords : Chitosan-PVA hydrogel, Zinc oxide nanoparticles, Boric acid cross linker, Antibacterial properties, Swelling properties.

ÖZ : Kitosan-PVA hidrojel örnekleri, değişik miktarda kitosan ile PVA’nın sırasıyla -20 °C'de 6 saat + 37 °C 2 saat süreyle ilk dondurma/çözülme döngüyle hazırlanmıştır. Bu örneklerin, 5 donma/çözülme döngülüyle hazırlanmış olması sonucundaki kristallindeki artışla son derece esnek hidrojeller oluşmuştur. Eşit miktarda borik asitle çaprazbağlanmış çeşitli örnekler gece boyunca NaOH çözeltisiyle muamele edilmiş ardından hidrojel memran 5 kez saf suda durulanarak temizlenmiş ve 24 saat + 80 ° C'de bir fırında kurutulmuştur.Çinko oksit nanopartikülleri içermeyen numunelerin Şişme yüzdeleri iki yolla belirlendi: Birincisi, değişik zaman aralığında bilinen miktarlardaki kuru örneklerin saf su içerisideki, ikincisi ise farklı tampon çözeltilerindeki 24 saatlik etkileşimleridir. Kinetiğinden pH arttıkça % şişmede artış gözlenirken, pH ın oldukça yüksek, bazik şartlarında ise düşüş gözlenmektedir. Sudaki örneklerinden PVA miktarının artması PVA’ün sudaki çözünebilmesi özelliğinden, kitosanın ise çözünmeme özelliğinden dolayı şişmeyi arttıracaktır. ZnO nanopartikülleri içeren ve içermeyen örnekler için antibakteriyel özellikler, öncelikle kitosanın ve PVA miktarlarının bakteri çoğalmasına etkisi ile, ikinci olarak bu örneklerin nanopartikül içermesi durumundaki bakteri çoğalmasını önleyici etkisi olup olmadığıyla belirlenmiştir. LB agar ortamı daha ince bir peptidoglikan membran sahip olan bir Gram negatif bakteridir ve E.coli bakteri kültürünün oluşturulması için kullanılmıştır. Yüksek miktarda kitosan içeren örneklerin diğer örneklere göre, bakteri çoğalmasına karşın daha fazla önleyici etkisi olmuştur ve bu önleyici etki nanopartikül ilavesiyle artış göstermiştir. Son olarak hazırlanan örneklerin analizleri SEM ve FTIR ile yapılmıştır. Anahtar Kelimeler: Kitosan-PVA hidrojel, Çinko oksit nanaopartikülleri, Borik asit çaprazbağlayıcı, Antibakteriyel özellikler, Şişme özellikleri
Master of Science in Chemistry. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Arts and Sciences, Dept. of Chemistry, 2015. Supervisor: Assoc. Prof. Dr. Mustafa Gazi.
Keywords: Chemistry; Chitosan-PVA hydrogel; Zinc oxide nanoparticles; Boric acid cross linker; Antibacterial properties; Swelling properties